BAHASA INGGRIS - Hanima, Sitti (Al-Hijrah: Journal of Islamic Economics And Banking, 2025)
This research aims to analyze the role of Sharia-based Fintech Peer to Peer (P2P) Lending in promoting economic justice in Indonesia. Using a normative juridical method and Amartya Sen’s theory of economic justice as a theoretical framework, the study explores literature, legal regulations, and current fintech practices. The findings show that while Sharia P2P Lending holds strong potential to expand financial access and empower MSMEs, significant challenges remain regarding sharia compliance, consumer protection, and regulatory clarity. The integration of Amartya Sen’s capability approach with Islamic economic principles highlights the importance of equitable access to finance in realizing just and inclusive economic development. The research emphasizes the need for comprehensive regulation, public financial literacy, and technological innovation aligned with Islamic legal values. It concludes that Sharia P2P Lending can become a strategic instrument to strengthen welfare and reduce inequality, provided it adheres to fair, transparent, and sharia-compliant financial practices.